Painting, poetry, and immortality in Benedetto Varchi's sonnets. Issue 4 (2nd October 2019) - Vatteroni, Selene Maria
Abstract: Benedetto Varchi's Due Lezzioni not only represent the high point of the debate on the paragone between painting and sculpture but also bring up the question of the comparison of painting and poetry. The present article investigates this topic in Varchi's sonnets, focusing on a rhetorically consistent series of poems addressed to the painter Agnolo Bronzino. In these texts, Varchi renovates the Petrarchan model of Rvf 77–78 by setting up a Neoplatonic dialectic between dentro as the domain of poetry and fuori as the domain of painting, thereby shifting the comparison from the field of their mimetic capacity to that of their glorifying and immortalizing function. The final suggestion is that Bronzino's renowned portrait of Laura Battiferri marks a turning point in the contemporary debate on the superiority of poetry or painting as well as in Varchi's opinion about it, opening the way to integration and collaboration between the two arts within the realm of the dentro .